Kesulitan Siswa Gaya Belajar Kinestetik dalam Menyelesaikan soal HOTS - Mei Wijayadi; Prasetyo Budi Darmono; Nila Kurniasih (SAP (Susunan Artikel Pendidikan), 2021)
HOTS problem is a problem with high difficulties level, so that advanced proficiency are required to solve those problems. However, there are students who get difficulties in solving HOTS problems. The difficulties of students in solving problems are varied. The difficulties are caused by many factors, one of them is student learning style. Student learning styles are categorized into three types, namely kinesthetic, auditorial and visual. This research was focused on kinesthetic learning style. This research used descriptive qualitative method, so it was purposed to describe the kinestethic students difficulties in solving HOTS problems. Data were collected by quistionnarie, test and field notes. Data were analized by Miles and Hubberman analysis technique, there were data reduction, data display and conclussions drawing. The research result was that kinesthetic student get difficulties on in understanding concept level for C4 level problem. The factor of students’ difficulties is that the students are not careful in solving problem.